PENGHIMPUNAN PENDAPATAN NGEFANS SAWERAN : MISTIK SEMAR MESEM PENYANYI DANGDUT (Studi pada Penyanyi Orkestra Melayu New Kendedes) - Prasetyo, Whedy (Universitas Airlangga, 2020)
This study aims to examine the activities of dangdut singers to collect their entertainment income.Activities by basing on mystical routines for semar mesem.The use of this mystic is in recognition of the singer's income. Recognition in the form of collection throughsaweran mechanism. The mechanism angefans saweran contribution is findings of this study. Qualitative methods with an ethnometodology approach was used in this study. The results revealed the mystical semar mesemthat was used as a